The impact of Semaphorin 4C/Plexin-B2 signaling on fear memory via remodeling of neuronal and synaptic morphology - Simonetti, Manuela; Paldy, Eszter; Njoo, Christian; Bali, Kiran Kumar; Worzfeld, Thomas; Pitzer, Claudia; Kuner, Thomas; Offermanns, Stefan; Mauceri, Daniela; Kuner, Rohini (Molecular psychiatry, 2021)
Aberrant fear is a cornerstone of several psychiatric disorders. Consequently, there is large interest in elucidation of signaling mechanisms that link extracellular cues to changes in neuronal function and structure in brain pathways that are important in the generation and maintenance of fear memory and its behavioral expression. Members of the Plexin-B family of receptors for class 4 semaphorins play important roles in developmental plasticity of neurons, and their expression persists in some areas of the adult nervous system. Here, we aimed to elucidate the role of Semaphorin 4C (Sema4C) and its cognate receptor, Plexin-B2, in the expression of contextual and cued fear memory, setting a mechanistic focus on structural plasticity and exploration of contributing signaling pathways. We observed that Plexin-B2 and Sema4C are expressed in forebrain areas related to fear memory, such as the anterior cingulate cortex, amygdala and the hippocampus, and their expression is regulated by aversive stimuli that induce fear memory. By generating forebrain-specific Plexin-B2 knockout mice and analyzing fear-related behaviors, we demonstrate that Sema4C-PlexinB2 signaling plays a crucial functional role in the recent and remote recall of fear memory. Detailed neuronal morphological analyses revealed that Sema4C-PlexinB2 signaling largely mediates fear-induced structural plasticity by enhancing dendritic ramifications and modulating synaptic density in the adult hippocampus. Analyses on signaling-related mutant mice showed that these functions are mediated by PlexinB2-dependent RhoA activation. These results deliver important insights into the mechanistic understanding of maladaptive plasticity in fear circuits and have implications for novel therapeutic strategies against fear-related disorders.
Veröffentlicht: 23 August 2019
Gesehen am 15.04.2020